2020
DOI: 10.3390/ma13071687
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Graphene Oxide Nanocomposite Membranes as Adsorbents with Applications in Water Purification

Abstract: The scope of this article is to develop composite membranes using chitosan (CS) and graphene oxide (GO) as adsorbents for the removal of inorganic pollutants such as heavy metal ions, particularly Pb2+, from aqueous solutions. GO was obtained by modified Hummers method and blended with CS solution. The introduction of ethylenediaminetetraacetic acid (EDTA) compound to CS/GO suspension lead to an increased adsorption capacity of CS/GO for the elimination of heavy metals by forming stable chelates with them. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 47 publications
(66 reference statements)
0
20
0
Order By: Relevance
“…GO was synthesized using the modified Hummer’s method presented in our previous literature reports (Scheme 1 presented in [ 26 , 27 ]). Different solutions were prepared at discrete concentrations, as shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…GO was synthesized using the modified Hummer’s method presented in our previous literature reports (Scheme 1 presented in [ 26 , 27 ]). Different solutions were prepared at discrete concentrations, as shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…They also mentioned that the GO-CS composite's system might be due to the presence of a covalent attachment made by the cross-linking of CS and GO, which limits the destruction of the amine parts in the CS. 56 As is well-known from the literature 57,58 and as conrmed from the present FTIR results, there is an interaction between the amino groups in the chitosan chains with the epoxy groups on the GO surface, resulting in the transformation of the primary amino (-NH 2 ) group to secondary (-NH-) groups, as previously reported by Cao et al 57 In addition, CS contains amine and hydroxyl groups, while GO surfaces are fully with various functionalities. Thus, there is an interaction between these groups to form hydrogen bonds.…”
Section: Ftir Analysis Of the Pure And Modied Samplesmentioning
confidence: 98%
“…They have shown that graphene oxide enhances the thermo-mechanical effects of polymeric membranes [ 210 ]. The GO presents functional groups on the surface that can transform into hydrophilic functional groups (-NH 2 , -OH, and -SO 3 H), which are useful in producing functionalized graphene oxide and graphene-based materials [ 211 , 212 ]. GO gained important consideration in applications regarding nanocomposite polymeric membranes for water treatment, inclusive in water purification, also examined as potential candidate for the removal of pharmaceuticals and organic molecules from water and wastewaters [ 212 , 213 ].…”
Section: Effect Of Nanomaterials On Polymeric Membranesmentioning
confidence: 99%
“…The GO presents functional groups on the surface that can transform into hydrophilic functional groups (-NH 2 , -OH, and -SO 3 H), which are useful in producing functionalized graphene oxide and graphene-based materials [ 211 , 212 ]. GO gained important consideration in applications regarding nanocomposite polymeric membranes for water treatment, inclusive in water purification, also examined as potential candidate for the removal of pharmaceuticals and organic molecules from water and wastewaters [ 212 , 213 ]. Like other nanofillers already presented in this paper, GO incorporation in polymeric membranes can bring significant change to the hydrophilic profile and improving also permeability performance [ 123 ].…”
Section: Effect Of Nanomaterials On Polymeric Membranesmentioning
confidence: 99%